Block hybrid multilevel method to compute the dominant λ-modes of the neutron diffusion equation. (November 2018) - Carreño, A.; Vidal-Ferràndiz, A.; Ginestar, D.; Verdú, G.
Highlights: Large generalized eigenvalue problems have to be solved to obtain the lambda modes. The inverse-free preconditioned Arnoldi method and the modified Newton method are used to compute them. A hybrid scheme based on these block methods is proposed. A multilevel technique is used to initialize the iterative eigenvalue solvers. Abstract: The dominant λ -modes associated with a nuclear reactor configuration describe the neutron steady-state distribution and its criticality. Furthermore, they are useful to develop modal methods to study reactor instabilities. Different eigenvalues solvers have been successfully used to obtain such modes, most of them are implemented reducing the original generalized eigenvalue problem to an ordinary one. Thus, it is necessary to solve many linear systems making these methods not very efficient, especially for large problems. In this work, the original generalized eigenvalue problem is considered and two block iterative methods to solve it are studied: the block inverse-free preconditioned Arnoldi method and the modified block Newton method. All of these iterative solvers are initialized using a block multilevel technique. A hybrid multilevel method is also proposed based on the combination of the methods proposed. Two benchmark problems are studied illustrating the convergence and the competitiveness of the methods proposed. A comparison with the Krylov-Schur method and the Generalized Davidson is also included.